Excitons into one-axis crystals of zinc phosphide (Zn₃P₂) - Stepanchikov, D.M.; Chuiko, G.P. (Condensed Matter Physics, 2009)
Theoretical study of excitons spectra is offered in this report as for Zn₃P₂ crystals. Spectra are got in the zero approach of the theory of perturbations with consideration of both the anisotropy of the dispersion law and the selection rules. The existence of two exciton series was found, which corresponds to two valence bands (hh, lh) and the conductivity band (c). It is noteworthy that anisotropy of the dispersion law plus the existence of crystalline packets (layers) normal to the main optical axis, both will permit the consideration of two-dimensional excitons too. The high temperature displaying of these 2D-exciton effects is not eliminated even into bulk crystals. The calculated values of the binding energies as well as the oscillator's strength for the optical transitions are given for a volume (3D) and for two-dimensional (2D) excitons. The model of energy exciton transitions and four-level scheme of stimulated exciton radiation for receiving laser effect are offered.